2022
DOI: 10.3390/ani12192507
|View full text |Cite
|
Sign up to set email alerts
|

Microsporidia as a Potential Threat to the Iberian Lynx (Lynx pardinus)

Abstract: Lynx pardinus is one of the world’s most endangered felines inhabiting the Iberian Peninsula. The present study was performed to identify the presence of microsporidia due to the mortality increase in lynxes. Samples of urine (n = 124), feces (n = 52), and tissues [spleen (n = 13), brain (n = 9), liver (n = 11), and kidney (n = 10)] from 140 lynxes were studied. The determination of microsporidia was evaluated using Weber’s chromotrope stain and Real Time-PCR. Of the lynxes analyzed, stains showed 10.48% and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
0
10
1
Order By: Relevance
“…In a seminal Spanish study, E. bieneusi was described for the first time in wild rabbits (del Aguila et al, 1999). Enterocytozoon bieneusi genotype D has also been identified in a farmed rabbit iso- (Izquierdo et al, 2022). Because rabbits are the staple prey for lynx in this region, these findings suggest that microsporidia-infected rabbits could pose a risk for Iberian lynx conservation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In a seminal Spanish study, E. bieneusi was described for the first time in wild rabbits (del Aguila et al, 1999). Enterocytozoon bieneusi genotype D has also been identified in a farmed rabbit iso- (Izquierdo et al, 2022). Because rabbits are the staple prey for lynx in this region, these findings suggest that microsporidia-infected rabbits could pose a risk for Iberian lynx conservation.…”
Section: Discussionmentioning
confidence: 93%
“…Of note, E. bieneusi and E. intestinalis (but not E. hellem or E. cuniculi ) were detected in kidney and/or brain tissues of wild European rabbits and Iberian hares in southern Spain, suggesting that meat consumption of infected animals can be of public health concern (Martínez‐Padilla et al, 2020). More recently, the critically endangered Iberian lynx has been shown to be infected by microsporidial pathogens by molecular and serological methods in southern Spain (Izquierdo et al, 2022). Because rabbits are the staple prey for lynx in this region, these findings suggest that microsporidia‐infected rabbits could pose a risk for Iberian lynx conservation.…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, microsporidia infection has been detected in humans [ 34 , 35 ], animals [ 6 , 19 , 29 , 36 ], and wastewater [ 37 , 38 ]. Previous studies identified E. cuniculi by PCR in an AIDS patient (genotype III) [ 35 ], Crohn’s disease patients [ 39 ], water samples from Madrid (genotypes I and III) [ 38 ], the Iberian lynx ( Lynx pardinus ) in southern Spain [ 40 ], and captive chimpanzees ( Pan troglodytes ) in Madrid (genotype I) [ 41 ], demonstrating the presence of this species in mainland Spain. Furthermore, other studies reported cases in domestic rabbits in Spain using indirect immunofluorescence testing [ 36 ], histopathological analysis [ 42 , 43 ], or serological analysis [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…E. hellem causes disseminated infections and has not been associated with diarrheal syndrome. It is commonly associated with keratoconjunctivitis and also affects respiratory and urinary systems [ 44 ]. Conversely to Enterocytozoonidae, both these species pertain to a family whose members are primarily terrestrial [ 36 ], suggesting that, in this case, fish are most probably acting as passive carriers.…”
Section: Discussionmentioning
confidence: 99%
“…E. cuniculi is the fourth most common microsporidian species found in humans. It can occasionally cause intestinal disease, but it is most commonly found affecting the brain and kidneys [ 44 ].…”
Section: Discussionmentioning
confidence: 99%